The effective library : report of the Hillingdon Project on Public Library Effectiveness - Totterdell, Barry; Bird, Jean (London : Library Association, 1976)
This text explore the effectiveness of public library in the UK. It give an insight to some of the basis of public library and how it has change the narrative for reading among the citizenry.
Includes bibliographical references and index.
ijb, 15/01/2019
Loans
Keywords: Public libraries